Does withdrawal from/remaining in an aggressor country affect companies’ ESG ratings? Case study of the Russia-Ukraine war - Dincă, Marius Sorin; Vezeteu, Cosmin-Dănuț; Dincă, Dragoș (Frontiers in Environmental Science, 2023)
As we mark one year since the start of the Russia-Ukraine war, countries and companies alike continue to adapt to this unprecedented disruption in the global economy and the subsequent uncertainty. One aspect that has not been thoroughly addressed from this conflict is its effect on companies’ ESG ratings and how the decision to remain or withdraw from Russia influences these ratings. To study this, a panel regression methodology on ESG data was applied on a significant number of companies before and after the start of the conflict. According to the results obtained, it would seem that insofar neither the overall ESG scores, nor the Social Scores are influenced by companies’ decisions to leave or to stay in Russia after 24-th of February 2022. We consider that these are not final outcomes and it will require further investigations and methodology improvements. The paper provides insights for ESG ratings providers, regulators and asset managers on the effects of companies’ decision to withdraw from/remain in an invading country on ESG ratings.